Oxidation of Benzylic and Aliphatic Secondary Alcohols to Carbonyl Compounds with KBrO3/CeCl3+7H2O System in Wet CH3CN - ZEYNIZADEH, BEHZAD; LOTFI, PARISA (Asian Journal of Chemistry, 2010)
Potassium bromate in presence of CeCl3·7H2O effectively oxidizes benzylic and aliphatic secondary alcohols to the corresponding carbonyl compounds i.e., primary alcohols selectively to aldehydes and secondary ones to ketones. The reactions are carried out in refluxing wet CH3CN within 1.5-8.0 h. This oxidation system is quite ineffective for the oxidation of aliphatic primary alcohols. The chemoselective oxidation of benzylic or aliphatic secondary alcohols over aliphatic primary alcohols is achieved perfectly with KBrO3/CeCl3·7H2O system.